2014
DOI: 10.1002/oti.1378
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Upper-body Dressing Scale in Japanese Patients with Vascular Dementia with Hemiparesis

Abstract: The purpose of this study was to examine the reliability and validity of the Upper-body Dressing Scale (UBDS) for buttoned shirt dressing, which evaluates the learning process of new component actions of upper-body dressing in patients diagnosed with dementia and hemiparesis. This was a preliminary correlational study of concurrent validity and reliability in which 10 vascular dementia patients with hemiparesis were enrolled and assessed repeatedly by six occupational therapists by means of the UBDS and the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Higher UBDS scores and longer UBDS time indicate poorer upper-body dressing performance. Excellent inter-rater (ICC = 0.999), intra-rater (ICC = 0.971), and test-retest (ICC = 0.87) reliabilities have been demonstrated for UBDS score in vascular dementia and stroke patients (7,8).…”
Section: Outcome Measures Upper-body Dressing Scale (Ubds)mentioning
confidence: 91%
See 3 more Smart Citations
“…Higher UBDS scores and longer UBDS time indicate poorer upper-body dressing performance. Excellent inter-rater (ICC = 0.999), intra-rater (ICC = 0.971), and test-retest (ICC = 0.87) reliabilities have been demonstrated for UBDS score in vascular dementia and stroke patients (7,8).…”
Section: Outcome Measures Upper-body Dressing Scale (Ubds)mentioning
confidence: 91%
“…As excellent inter-rater (ICC = 0.971) reliability has been reported for UBDS score for patients with vascular dementia and stroke (7), the ICC for chronic stroke patients was assumed to be 0.9. As no previous study has evaluated correlations between UBDS and stroke-specific outcome measures for chronic stroke patients, a medium correlation was assumed (ρ = 0.30).…”
Section: Sample Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in recent years, epidemiological studies suggested that the incidence of rotator cuff tear was almost 17-41% in the mid and old aged, and was still rising [1].This was related to the aging and the popularity of national tness in China. With the development of health care, arthroscopic rotator cuff repair has become the "golden standard" for the treatment of rotator cuff tear, which had the advantage of slight injury and few complications [2].…”
Section: Introductionmentioning
confidence: 99%